House prices and the distribution of wealth around the great recession - Richard Cóndor; Rodolfo Oviedo Moguel (Banco de México, 2023)
This paper employs a calibrated model of the US economy to analyze the boom and bust in house prices as well as the shifts in the distribution of wealth during the years around the Great Recession. We replicate the dynamics of the housing market using shocks to aggregate income, the distribution of income, credit conditions, and expectations of future housing demand driven by irrational exuberance. We find that irrational exuberance was the primary driver behind the dynamics of house prices and that the relaxation and subsequent tightening of credit conditions are crucial to explain the behavior of mortgage debt, default rates, and housing holdings by households at the bottom of the wealth distribution. The boom in house prices led to a temporary decrease in wealth concentration, which was subsequently reversed during the bust.
Keywords: E21; E32; G01; R31; D31; D84; 330; Credit Conditions; Expectations; Great Recession; Irrational Exuberance; House Prices